THE MEDIATING ROLE OF ABSORPTIVE CAPACITY IN THE RELATIONSHIP OF KNOWLEDGE SHARING AND INNOVATION PERFORMANCE IN MSMES - Wulandari Dyah Pitaloka; Tina Rahayu (Universitas Maarif Hasyim Latif, 2023)
The purpose of this study is to analyze the mediating role of knowledge sharing in the relationship between knowledge sharing and innovation performance in MSMEs. The research used in the study used explanatory with a quantitative approach. The population in this study were all MSMEs in the fashion sector in Rembang Regency totaling 230 MSMEs. The sampling technique in this study was nonprobability sampling. The method used was purposive sampling where researchers used an assessment of certain criteria in conducting research. The number of samples taken in this study was 70 MSMEs in the fashion sector that have been operating for at least 1 year. Respondents in this study were fashion MSMEs in Rembang Regency. The data analysis technique in this study used Partial Least Square (PLS) with the help of SmartPLS software. The results showed that knowledge sharing has a significant positive effect on innovation performance. Knowledge sharing has a significant positive effect on absorptive capacity. Absorptive capacity has a significant positive effect on innovation performance. Knowledge sharing has a significant positive effect on innovation performance mediated by absorptive capacity.